A moving boundary problem with space-fractional diffusion logistic population model and density-dependent dispersal rate - Kumar A.; Rajeev (My University, 2025)
In this article, we discuss a space-fractional diffusion logistic population model with Caputo fractional derivative and density-dependent dispersal rate. The numerical solution of the problem is obtained by using a finite difference scheme. The consistency and stability of the scheme for our solution to the problem are also discussed. The effect of the density-dependent dispersal rate and order of the space-fractional derivative are analyzed for the population density and expanding front (moving boundary). © 2020 Elsevier Inc.